Optimizing the Knuckle Corner Design of an Urban EV8 Vehicle Category Concept to Meet Turning Radius Requirements - Nurhadi, Idham; Ramdhani, Ramdhani; Mubarak, Ibnu (Universitas Negeri Padang, 2023)
This research aims to achieve the smallest possible turning radius for the knuckle joint while also meeting the regulations set by the Shell Eco-Marathon (SEM) committee regarding the design angles and lengths. Calculations and testing are conducted using simulation methods to obtain suitable angles and lengths for the knuckle. This simulation method involves a series of analyses to obtain data such as static turning radius diagrams, followed by an analysis using the camber calculation formula. The shape, angle, length, and design of the knuckle are considered with regard to driving safety factors. The findings of this study indicate that for a six-meter turning radius, the outer wheel requires a steering angle of δ_0=10.868°, and the inner wheel requires a steering angle of δ_i=77.397°. After improvements, for a 5.5-meter turning radius, the outer wheel requires a steering angle of δ_0=15.960°, and the inner wheel requires a steering angle of δ_i=71.321°. It can be concluded that this design can optimize the performance of the knuckle steering system.